Optimization of residential building construction time using the critical path method in bontang - Zuhriah, Zuhriah; Nurhasanah, Andi; Putri, Nadia Surya; Shavira, Try Gita; Jelita, Auldy Putri (Institute of Computer Science (IOCS), 2025)
The construction of residential housing is a complex process that requires optimal time management to ensure timely project completion. Delays in construction project implementation are often caused by various internal and external factors, such as limited resources, weather conditions, and challenges in coordinating project activities. This research aims to optimize the construction duration of a type 130 residential house in Bontang City through the application of the Critical Path Method (CPM). This method functions to identify the critical path in the stages of project activities and determine the estimated minimum project completion duration. Project activity data were obtained through field observations and interviews with the project implementers, then analyzed using the CPM approach by calculating Early Start (ES), Early Finish (EF), Late Start (LS), and Late Finish (LF). The analysis results indicate that by identifying and managing the critical path, the project—which was initially estimated to take 166 days—can be completed in 135 days with a total of 13 main activities, resulting in a time acceleration of 31 days. This study demonstrates that the CPM method is effective in controlling project execution time and has the potential to serve as a strategic solution to minimize delays in similar future projects